KUALITAS PELAYANAN PADA RESTORAN KHAS MELAYU PONDOK YURIKA PEKANBARU - Loly Ayuni Putri; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research purpose to know how service quality in the special malay restaurant PondokYurika. And to know too barriers in doing excellent service to consumer. Research method used in this research is descriptive method, what porpuse to depict fact by telling of a circumstance, do not explain relstion, not check hypothesis or make prediction. This research is scale likert, that is scale designed to enable responder reply various level in each measured object.Boundaries problem in this research just about Service Quality and it barriesin the Pondok Yurika Restaurant. Outside of that aspect do not researchers. Identification of this research is howService quality provided by the Special Malay RestaurantPondokYurikaPekanbaru . And what factors are most dominant by consumers in excellent service to give by restaurant Pondok Yurika with used SERVQUAL method.Keywords : Tangibles, Emphaty, Responsiveness, Realibility and Assurance.